The PKN1- TRAF1 signaling axis as a potential new target for chronic lymphocytic leukemia. (1st January 2021) - Edilova, Maria I.; Law, Jaclyn C.; Zangiabadi, Safoura; Ting, Kenneth; Mbanwi, Achire N.; Arruda, Andrea; Uehling, David; Isaac, Methvin; Prakesch, Michael; Al-awar, Rima; Minden, Mark D.; Abdul-Sater, Ali A.; et al.
ABSTRACT: TRAF1 is a pro-survival adaptor molecule in TNFR superfamily (TNFRSF) signaling. TRAF1 is overexpressed in many B cell cancers including refractory chronic lymphocytic leukemia (CLL). Little has been done to assess the role of TRAF1 in human cancer. Here we show that the protein kinase C related kinase Protein Kinase N1 (PKN1) is required to protect TRAF1 from cIAP-mediated degradation during constitutive CD40 signaling in lymphoma. We show that the active phospho-Thr774 form of PKN1 is constitutively expressed in CLL but minimally detected in unstimulated healthy donor B cells. Through a screen of 700 kinase inhibitors, we identified two inhibitors, OTSSP167, and XL-228, that inhibited PKN1 in the nanomolar range and induced dose-dependent loss of TRAF1 in RAJI cells. OTSSP167 or XL-228 treatment of primary patient CLL samples led to a reduction in TRAF1, pNF-κB p65, pS6, pERK, Mcl-1 and Bcl-2 proteins, and induction of activated caspase-3. OTSSP167 synergized with venetoclax in inducing CLL death, correlating with loss of TRAF1, Mcl-1, and Bcl-2. Although correlative, these findings suggest the PKN1-TRAF1 signaling axis as a potential new target for CLL. These findings also suggest the use of the orally available inhibitor OTSSP167 in combination treatment with venetoclax for TRAF1 overexpressing CLL.